Pulmonary Hypoplasia in Jarcho-Levin Syndrome - Rodríguez, Luis M.; García-García, Inés; Correa-Rivas, María S.; García-Fragoso, Lourdes (Puerto Rico Health Sciences Journal, 2004)
Jarcho-Levin syndrome, also known as spondylothoracic dysplasia and characterized by short trunk dwarfism, “crab-like” rib cage, with ribs and vertebral defects; it is not uncommon in Puerto Ricans. Many patients die in early infancy due to respiratory compromise associated to lung restriction and the reported cases emphasize mostly the skeletal malformations associated to the syndrome. We report the autopsy findings in a newborn with isolated Jarcho-Levin syndrome emphasizing pulmonary pathology. He was a pre-term male who died of respiratory failure at three hours old and, autopsy findings confirmed the clinical diagnosis. Internal examination showed hypoplastic lungs with normal lobation. The histological structure appeared normal and relatively mature; the diaphragm showed eventration and unilateral absence of musculature. This case shows the worst spectrum of the Jarcho-Levin syndrome: pulmonary hypoplasia not compatible with extrauterine life. Since thoracic restriction is present during the fetal period, the degree of pulmonary hypoplasia probably defines survival beyond the neonatal period.